Extraintestinal Manifestations of Pediatric Inflammatory Bowel Disease: Prevalence, Presentation, and Anti-TNF Treatment - Greuter, Thomas; Bertoldo, Fabio; Rechner, Roman; Straumann, Alex; Biedermann, Luc; Zeitz, Jonas; Misselwitz, Benjamin; Scharl, Michael; Rogler, Gerhard; Safroneeva, Ekaterina; Ali, Raja A R; Braegger, Christian; et al. (Journal of pediatric gastroenterology and nutrition, 2017)
There is a paucity of data on extraintestinal manifestations (EIM) and their treatment in pediatric patients with inflammatory bowel disease (IBD). Since 2008, the Pediatric Swiss IBD Cohort Study has collected data on the pediatric IBD population in Switzerland. Data on 329 patients were analyzed retrospectively. A total of 55 patients (16.7%) experienced 1-4 EIM (39 Crohn disease, 12 ulcerative colitis, and 4 IBD-unclassified patients). At IBD onset, presence of EIM was more frequent than in the adult population (8.5% vs 5.0%, P = 0.014). EIM were more frequent in Crohn disease when compared to ulcerative colitis/IBD-unclassified (22.5% vs 10.3%, P = 0.003). The most prevalent EIM were peripheral arthritis (26/329, 7.9%) and aphthous stomatitis (24/329, 7.3%). Approximately 27.6% of all EIM appeared before IBD diagnosis. Median time between IBD diagnosis and occurrence of first EIM was 1 month (-37.5-149.0). Thirty-one of the 55 patients (56.4%) were treated with 1 or more anti-tumor necrosis factor (TNF) agents. IBD patients with EIM were more likely to be treated with anti-TNF compared to those without (56.4% vs 35.0%, P = 0.003). Response rates to anti-TNF depended on underlying EIM and were best for peripheral arthritis (61.5%) and uveitis (66.7%). In a cohort of pediatric patients with IBD, EIM were frequently encountered. In up to 30%, EIM appeared before IBD diagnosis. Knowledge of these findings may translate into an increased awareness of underlying IBD, thereby decreasing diagnostic delay. Anti-TNF for the treatment of certain EIM is effective, although a substantial proportion of new EIM may present despite ongoing anti-TNF therapy.